An evaluation of the effectiveness of the Integrated Development Plan on service delivery with reference to the Emfuleni Local Municipality in Gauteng - Mukwevho, Hulisani Cedric (My University, 2012)
The study has been prompted by the initiative of the Local Government of South Africa in introducing the Integrated Development Plan in local municipalities in 1998 as an interim integrated plan. Local Municipalities in South Africa have to use “integrated development planning” as a method of planning for future developments in their areas. Apartheid planning left South Africa with cities and towns that have racially divided business and residential areas; are badly planned to cater for the poor; have long travelling distances to work and poor access to business and other services; have great differences in levels of service delivery between rich and poor areas; have sprawling informal settlements and spread-out residential areas that make cheap service delivery difficult. Rural areas were left underdeveloped and largely unserviced. The aim of the study was to evaluate the impact of the IDP on service delivery in Emfuleni Local Municipality. The objectives of this study were: to evaluate the effectiveness of the IDP on service delivery and its implementation; to assess the capacity of the municipality to meet the IDP objectives and targets; to investigate the perceptions of the Emfuleni Local Municipality ward and Proportional Representative (PR) Councillors on their mandate and service delivery; and to identify and recommend strategies to enhance the effectiveness of the IDP on service delivery. The study was qualitative in design and collected data using interviews. The study found out that the public participation process, the Integrated Development Plan, service delivery protests and state of service delivery in Emfuleni has clearly shown that the Emfuleni Integrated Development Plan does not have significant impact on service delivery. Based on the findings of the study, the following recommendations are made: that there should an alignment of projects with community needs, establishment of a monitoring and evaluation unit, strengthen the intergovernmental relations system and regular feedback, communication and interaction with communities. These systems and structures will ensure that there is regular and coherent participation and involvement of the community as far as possible.
Thesis (M.Dev.) -- University of Limpopo, 2012
Keywords: Service delivery; Integrated Development Plan; Municipal services -- South Africa -- Gauteng; Local government -- South Africa -- Gauteng; Municipal government -- South Africa -- Gauteng